1995
DOI: 10.1089/thy.1995.5.425
|View full text |Cite
|
Sign up to set email alerts
|

Thyrotropic Action of Human Chorionic Gonadotropin

Abstract: Hyperthyroidism or increased thyroid function has been reported in many patients with trophoblastic tumors. In these cases, greatly increased human chorionic gonadotropin (hCG) levels and suppressed TSH levels suggest that hCG has thyrotropic activity. Recent investigations have clarified the structural homology not only in the hCG and TSH molecules but also in their receptors, and this homology suggests the basis for the reactivity of hCG with the TSH receptor. The clinical significance of the thyrotropic act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
147
0
4

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 317 publications
(154 citation statements)
references
References 68 publications
3
147
0
4
Order By: Relevance
“…These cases, considerably increased hCG levels and suppressed TSH levels suggest that hCG has thyrotropic activity. Human chorionic gonodotropine and human TSH belong to the biochemically closely related glycoprotein hormone family, they are potentially cross-reactive at the receptor level (8). In vitro, hCG has a weak intrinsic thyroid-stimulating activity, being able to stimulate iodine uptake, generation of cAMP, 3,5,3'-triodothyronine secretion, and even growth of thyroid cells (19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These cases, considerably increased hCG levels and suppressed TSH levels suggest that hCG has thyrotropic activity. Human chorionic gonodotropine and human TSH belong to the biochemically closely related glycoprotein hormone family, they are potentially cross-reactive at the receptor level (8). In vitro, hCG has a weak intrinsic thyroid-stimulating activity, being able to stimulate iodine uptake, generation of cAMP, 3,5,3'-triodothyronine secretion, and even growth of thyroid cells (19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%
“…These studies showed that hCG is the molar TSH and that 1 Unite hCG has intrinsic thyrotrophic activity equivalent to approximately 0.5 µU TSH in the Mouse bioassay (4). Additionally, hCG stimulates iodide uptake, adenylate cyclase, and DNA synthesis in cultured rat thyroid cells (8). Many investigations have detected that hCG and TSH share not only structural homology but also their receptors show structural similarity as well, and this homology suggests the basis for the reactivity of hCG with the TSH receptor (9,10).…”
Section: Solated Hypogonadotropic Hypogonadism (Ihh)mentioning
confidence: 96%
“…However, LHR and FSHR are also orthologous with the DLRG1, but cannot bind to thyrostimulin. Furthermore, mammalian gonadotropins are capable of activating the teleost TSHR, whilst hCG possesses thyrotrophic abilities (Yoshimura and Hershman 1995;MacKenzie et al 2009). Consequently, the specifi city of TSHR for its ligands is not as high as that of other glycoprotein receptors.…”
Section: Th E Unique Structure Of Thyrostimulinmentioning
confidence: 99%
“…22 f. HCG is the thyroid stimulator of pregnancy. 23 Numerous studies of thyroid hormones in pregnancy have established an association between transient biochemical hyperthyroidism and NVP. The degree of biochemical hyperthyroidism correlates closely with the severity of NVP.…”
Section: The Fundamental Stimulusmentioning
confidence: 99%